Asthma history predicts the risk of affective disorders and anxiety disorders - Liang, Wenbin; Chikritzhs, Tanya (Scientific Research Publishing, 2013)
Background: Positive associations between asthma and a range of mental disorders have been increasingly reported in cross-sectional studies. It is important to determine whether the association between asthma and mental disorders may be causal. Objectives: We conducted a retrospective cohort study using data collected from the 2007 Australia Mental Health and Wellbeing survey (MHW) to examine whether preexisting asthma may predict the likelihood of various types of anxiety disorders and affective disorders. Design, Settings and Subjects: The 2007 MHW survey was a nationally representative household survey. Its data included 8841 Australian adults aged 18 - 85 yrs. Age at first onset of asthma and mental disorders were used to reveal the order of occurrence of asthma and mental disorders, and to define time at risk and asthma exposure. Kaplan-Meier failure function and multivariate Poisson regression models were employed in analysis. Results: Participants who had a history of asthma that lasted six months or more were at higher risk of panic disorder, obsessive compulsive disorder, posttraumatic stress disorder, bipolar disorder, mania and hypomania. The association between asthma history and risk of mental disorder subtypes differed by gender. Conclusion: The findings of this study support the hypothesis that pre-existing asthma increases the risk of a number of anxiety disorders and affective disorders. Predisposition to carbon dioxide hypersensitivity and corticosteroid therapy may partly explain the observed associations.